PREVALENCE AND ECOLOGICAL RISK OF POLYCHLORINATED BIPHENYLS (PCBS) IN AGRICULTURAL SOILS OF DADIN KOWA DAM BASIN, GOMBE STATE NIGERIA - Usman, Y. M; Saidu, Umar; E. F, Baka; Maria, A. A; Takkani, S. J (FUDMA Journal of Sciences, 2025)
Pesticide residues are “forever chemicals” considered to be pollutants of environmental and human health. The study was aimed at analysing the PCBs pesticides residue composition of four different soil samples from selected areas of Dadin kowa Dam Basin where agricultural activities dominated their occupation. Physicochemical parameters such as the pH of soil samples were analysed and showed pH values range from 7.54 in Sb3 to 7.21 in Sb2. The conductivity of the soil sample ranging from 337.25 µScm-1 inSb4 to 178 µScm-1 in Sb3.The soil texture analysis investigated showed Sb1 has the highest percentage of sand with 44.44% and soil sample Sb2 has highest percentage of slit soil at 40.90% while soil sample Sb4 has the highest percentage of clay soil with 41.66%. The PCBs composition of soil samples was determined showed that 2,2,3,4,4,5,6-Heptachlorobiphenyl in sample Sb3 revealed highest composition of 0.25 ppm concentration while 2-Chlorobiphenyl in all samples Showed the least composition of 0.00 ppm concentration. The result of soil the analysed at Dadinkowa Dam Basin was free from threats of pollutants residues investigated except Sb3 soil were below the permissible value range of 0.1 to 0.6 ppm.